SISTEM INFORMASI LAPORAN PENJUALAN BERBASIS WEBSITE PADA PT. WIDYA WASKITA WIJAYA CABANG CILACAP - Carolina Ety Widjayanti (Universitas Methodist Indonesia, 2020)
Widya Waskita Wijaya Cilacap Branch is an official agent of PT. Pertamina (Persero) which is headquartered in Semarang. This company is engaged in the sale of non-subsidized fuel for the industrial sector, transportation, contractors, mining, plantations, ships, and so on. The main problems that exist at PT. Widya Waskita Wijaya Cilacap Branch is a fuel sales reporting process that uses a document delivery agent so it takes several days to get to the Semarang head office. With this problem, the Semarang head office wanted a web-based information system that could speed up the reporting process of fuel sales from the Cilacap branch office to the Semarang head office. The system development method used is the waterfall model with system development tools in the form of context diagrams, DFD, normalization, and ERD. Meanwhile, the making of this information system uses the PHP programming language, using Dreamweaver software as the editor and Navicat as the database. By using this information system, the process of making fuel bidding letters and fuel sales receipts is more effective and accelerates the reporting process of fuel sales to the Semarang head office.